Biodiversity of freshwater organisms in urban water bodies (Zoological Records and Reviews, 2022)
Urban freshwater bodies -- including city lakes, retention ponds, ornamental tanks, storm-water basins, and urban canalsystems -- represent a globally expanding habitat type whose biodiversity is poorly documented relative to their potentialecological significance. While urban water bodies are frequently dismissed as degraded and ecologically depauperate,emerging evidence from European cities suggests they can support unexpectedly diverse macroinvertebrate andmacrophyte assemblages and serve as refugia for certain freshwater taxa in heavily urbanised landscapes. This studypresents a comprehensive multi-taxon biodiversity survey of freshwater organisms across 48 urban water bodies in threeAsian megacities -- Hyderabad, India; Colombo, Sri Lanka; and Dhaka, Bangladesh -- using standardised protocols forphytoplankton, zooplankton, macroinvertebrates, macrophytes, and fish. A total of 684 freshwater taxa are documentedacross all groups and cities, comprising 184 phytoplankton taxa, 128 zooplankton taxa, 212 macroinvertebrate species,84 macrophyte species, and 76 fish species. Urban water body age, connectivity to natural water bodies, andsurrounding green cover are the strongest predictors of total biodiversity. Hyderabad's historic tank system -- a networkof over 3,000 interconnected water bodies -- supports the highest per-water-body biodiversity of the three cities. Invasivespecies -- particularly Eichhornia crassipes, Gambusia affinis, and Pomacea canaliculata -- are documented in 68.8% ofsurveyed water bodies and are identified as a major threat to native biodiversity. Management recommendations forenhancing urban freshwater biodiversity are provided.
Keywords: freshwater conservation; urban ecology; Hyderabad tanks; invasive species; zooplankton; phytoplankton; macroinvertebrates; biodiversity; water bodies; urban freshwater